1996
DOI: 10.1002/chem.19960020812
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Structural Studies of Highly Enantioselective Mn(salen) Epoxidation Catalysts

Abstract: Abstract:The relationship between catalyst structure and enantioselectivity in the asymmetric epoxidation of unfunctionalized olefins by a series of chiral Mn (sa1en) complexes (1 -10) was examined. The Xray structures of 5-coordinate complexes 5, 8, of 6-coordinate 9 ([6,6 = -fBu; 4,4 = -tBu]+CIO;), and 10 (6,6 = -fBu; 4.4 = -Br ) were determined. Catalysts 1 -9 were derived from (R,R)-1 ,tdiaminocyclohexane and catalyst 10 from (S,S)-1,2-diphenylethyIenediamine. Catalysts 1-9 differ in the stereoelectronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 41 publications
4
59
0
6
Order By: Relevance
“…In the case of classical Mn-salen complexes, it has been proven that the geometry around the metal center was square planar in the case of cationic complexes with two residual ligands in apical positions, trans to each other or slightly square pyramidal in the case of neutral complexes with the residual ligand perpendicular to the plane. 24 Che has shown 15d that, in the case of binaphthyl-salen manganese complexes, the geometry, established by X-ray crystallography around the manganese atom, was octahedral with the Schiff base ligand bound to the metal center in a cis-β configuration, as shown on Scheme 5. The binaphthyl moiety enforces the complexes to adopt a non-square-planar geometry.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of classical Mn-salen complexes, it has been proven that the geometry around the metal center was square planar in the case of cationic complexes with two residual ligands in apical positions, trans to each other or slightly square pyramidal in the case of neutral complexes with the residual ligand perpendicular to the plane. 24 Che has shown 15d that, in the case of binaphthyl-salen manganese complexes, the geometry, established by X-ray crystallography around the manganese atom, was octahedral with the Schiff base ligand bound to the metal center in a cis-β configuration, as shown on Scheme 5. The binaphthyl moiety enforces the complexes to adopt a non-square-planar geometry.…”
Section: Resultsmentioning
confidence: 98%
“…It has thus been suggested that the most stable electronic configuration of Mn(III) would involve having all four d electrons unpaired, yielding a quintuplet state. However, the fact that the salen ligand assumes a slightly bent conformation [28] and the effect of axial coordination by a donor ligand may alter this outcome. A triplet (two unpaired d electrons) or a singlet (no unpaired electrons) ground state may therefore be a viable hypotheses [29][30][31].…”
Section: Ground State Spin Multiplicity Of Mn(salen) Speciesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Recent studied have demonstrated that manganese complexes in combination with various oxidizing reagents catalyze a range of oxidation reactions, oxygenation of saturated [18][19][20][21][22][23] and aromatic hydrocarbons. [24][25][26][27] Although many studies performed on the oxidation of hydrocarbons by using Mn(III) complexes [28][29][30][31][32][33][34][35] and various peroxide substances as oxidants, there are few which used H 2 O 2 as a source of oxygen in the C-H oxidation of alkanes. 36 In recent decades, hydrogen peroxide has provoked significant interest in synthetic community and demonstrated to be a promising oxidant in organic synthesis since the oxidizing agent is economic, environmentally benign and powerful.…”
Section: Introductionmentioning
confidence: 99%